EFFECT OF WEATHER ON MUSTARD DYNAMICS UNDER SEMI-ARID ENVIRONMENT - NEOG, PRASANTNA; CHAKRAVARTY, N.V.K.; Sharma, M.K.; BHAGAWATI, GOUTOM; SRIVASTAVA, A.K. (Annals of Agricultural Research, 2014)
Field experiments were carried out on sandy loam soil of Indian Agricultural Research Institure (New Delhi) farm area with mustard cultivars Pusa Jaikisan and Varuna which were grown for two consecutive rabi seasons (2000-2001 and 2002-2003) at ten different dates following recommended agronomic practices. Irrespective of sowing dates and crop season LAI, CGR, PGR, total biomass and seed yield were higher in Pusa Jaikisan than in Varuna. Values of crop growth parameters and seed yield were maximum when crop was sown between 15th and 29th October in both the cultivars and seasons which might be due to crop sown in this period were exposed to the optimum thermal environment for growth and development. The value of LAI, total biomass production, CGR and PGR were higher in first crop season than the second crop season in all sowing dates in both the cultivars. A significant reduction of seed yield both in Pusa Jaikisan and Varuna in second season was probably due to prevailing cold spell coupled with low bright sunshine hours during the month of January and February, 2003 that might have caused reduction in LAI, CGR, PGR and biomass production resulting lower seed yield.